The achievement gap between learners who are assessed in a primary language and those assessed in a non-primary language in the natural sciences learning area - Sedibe, Godwin Konotia Bully (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Sociology and Social Anthropology))--University of Stellenbosch, 2009.